CORRELATION OF TNF-ALFA INFLAMMATION BIOMARKER LEVELS WITH THE INDONESIAN VERSION OF MONTREAL COGNITIVE ASSESSMENT (MOCA-INA) SCORES IN LAKUNAR ISCHEMIC STROKE PATIENTS - Hamdani, Faishol; Hartono, Jimmy Eko Budi; Tugasworo, Dodik; Retnaningsih, Retnaningsih; Suryawati, Herlina; Puspitawati, Arinta (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Tumor Necrosis Factor-Alpha (TNF-α) is a pro-inflammatory cytokine that is responsible for modulation the immune system. TNF-α is another important mediator involved in stroke pathophysiology. Cerebral small vessel disease (CSVD) is a major cause of lacunar ischemic stroke. In stroke there is an increase in TNF-α levels where post-stroke neuroanatomic damage can cause cognitive impairment. Objective: Proving the relationship between TNF-α serum levels on the day 3 of onset and the Moca Ina score on the day 7 of onset, day 30, and the difference in MoCa-INA scores and analyzing the relationship of risk factors cognitive function in lacunar ischemic stroke patients. Methods: An analytical observational study with a prospective cohort approach. Subjects were first-time lacunar ischemic stroke with blood sampling on the day 3 of onset to evaluate TNF-α levels. Cognitive function was examined by the MoCa-INA score which was evaluated on day 7 and day 30. Eta correlation test to connect TNF-α levels with MoCa-INA scores. Bivariate and multivariate analyzes used between the MoCa-INA score and other confounding factors. Results: There was a strong correlation between TNF-α levels on day 3 of onset and MoCA-INA on day 7 (ƞ= 0.972), a very strong correlation was found between TNF-α levels on day 3 of onset and MoCA-INA on day 30 (ƞ= 1,000), and there was a strong correlation between TNF-α levels on day 3 of onset and the difference between MoCA-INA (ƞ=0.905). there is a confounding variable diabetes mellitus that affects the 7th day of MoCA-INA. In the sub-analysis study, the mean serum TNF-α level on cognitive impairment on day 30 was higher than on day 7 with the most dominant domains being visuospatial and executive. Conclusion: There is a strong relationship between serum TNF-α levels and MoCa-INA scores in lacunar ischemic stroke patients, and there is one confounding variable of diabetes mellitus that affects the MoCa-INA score on the 7th day of examination.